2012
DOI: 10.1038/labinvest.2011.158
|View full text |Cite
|
Sign up to set email alerts
|

Histamine stimulates the proliferation of small and large cholangiocytes by activation of both IP3/Ca2+ and cAMP-dependent signaling mechanisms

Abstract: Although large cholangiocytes exert their functions by activation of cyclic adenosine 3′,5′-monophosphate (cAMP), Ca2+-dependent signaling regulates the function of small cholangiocytes. Histamine interacts with four receptors, H1–H4HRs. H1HR acts by Gαq activating IP3/Ca2+, whereas H2HR activates Gαs stimulating cAMP. We hypothesize that histamine increases biliary growth by activating H1HR on small and H2HR on large cholangiocytes. The expression of H1–H4HRs was evaluated in liver sections, isolated and cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
117
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 54 publications
(122 citation statements)
references
References 53 publications
(149 reference statements)
5
117
0
Order By: Relevance
“…26,34,44,45 After BDL, the biliary epithelium proliferates and cholangiocytes secrete abundant amounts of these neuroendocrine factors to support the increased demands of the proliferating biliary tree. 26,34,44 We have previously shown that (i) histamine treatment increases normal rat cholangiocyte proliferation; 28 and (ii) after BDL, histamine levels are increased in both serum and cholangiocyte supernatant. 7 Autocrine regulation by histamine has been demonstrated in both biliary hyperplasia and neoplasia, as evidenced by our finding that inhibition of HDC decreases biliary growth.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…26,34,44,45 After BDL, the biliary epithelium proliferates and cholangiocytes secrete abundant amounts of these neuroendocrine factors to support the increased demands of the proliferating biliary tree. 26,34,44 We have previously shown that (i) histamine treatment increases normal rat cholangiocyte proliferation; 28 and (ii) after BDL, histamine levels are increased in both serum and cholangiocyte supernatant. 7 Autocrine regulation by histamine has been demonstrated in both biliary hyperplasia and neoplasia, as evidenced by our finding that inhibition of HDC decreases biliary growth.…”
Section: Discussionmentioning
confidence: 97%
“…25,28 Virtually pure cholangiocytes (verified by g-glutamyltranspetidase histochemistry 29 ) were isolated as described by us 25,26 using a monoclonal antibody (a mouse IgG 2a , a gift from Dr R Faris, Brown University, Providence, RI, USA) against an unidentified antigen expressed by all rat cholangiocytes. Cell viability was evaluated using trypan blue.…”
Section: In Vivo Modelsmentioning
confidence: 99%
See 3 more Smart Citations